Australia as a Middle Power: Challenging the Narrative of Developed/Developing States in International Negotiations Surrounding Marine Genetic Resources. (26th May 2021) - Beringen, Ethan; Liu, Nengye; Lim, Michelle
Abstract: To date, marine genetic resources (MGR) have proven to be the most controversial aspect of the package deal structure of the ongoing negotiations of a legally binding instrument for the conservation and sustainable use of biodiversity beyond national jurisdiction (BBNJ). This has led to a proliferation of scholarly work characterizing the debate on MGR along developed and developing state lines. By applying middle power international relations theory to the Australian delegation's conduct in MGR negotiations, this article aims to challenge the developed/developing state narrative. As such, it advocates a more nuanced approach to understanding state motivation in multilateral treaty negotiations pertaining especially to complex issues such as MGR.